Words, books, images, and the long eighteenth century : essays for Allen Reddick - Zlatar, Antoinina Bevan; Ittensohn, Mark; Steiner, Enit Karafili; Timofeeva, Olga; Reddick, Allen Hilliard (FILLM studies in languages and literatures, 2021)
"The essays collected in this volume engage in a conversation between lexicography, the culture of the book, and the canonization and commemoration of English literary figures and their works in the long eighteenth century. The source of inspiration for each piece is Allen Reddick's scholarship on Samuel Johnson (1709-1784), the great English lexicographer whose Dictionary (1755) included thousands upon thousands of illustrative quotations from the "Best" authors, and more recently, Thomas Hollis (1720-1774), the much less well-known bibliophile who sent gifts of books by a pantheon of Whig authors to individuals and libraries in Britain, Protestant bastions in continental Europe, and America. Between the covers of Words, Books, Images readers will encounter canonical English authors of prose and poetry-Bacon, Milton, Defoe, Dryden, Pope, Richardson, Swift, Byron, Mary Shelley, and Lear. But they will also become acquainted with the agents of their canonization and commemoration-the printers and publishers of Grub Street, the biographer John Aubrey, the lexicographer and biographer Johnson, the bibliophile Hollis, and the portrait painter Reynolds. No less crucially, they will meet fellow readers of then and now-women and men who peruse, poach, snip, and savour a book's every word and image"--